Comparative performance of a solar assisted heat pump dryer with a heat pump dryer for Curcuma - R. Hasibuan; M Yahya; H. Fahmi; Edison Edison (Institute of Advanced Engineering and Science, 2020)
This study evaluated the performances of solar assisted heat pump dryer (SAHPD) and heat pump dryer (HPD) for drying of Curcuma xanthorrhiza Roxb. The HPD and SAHPD reduced mass of Curcuma from 30.70 kg to 7.85 kg needed 10.5 hours and 8 hours with average temperature and relative humidity 49.2oC and 26.5%, and 57.7oC and 19.8%, for SD and SAHPD respectively. The moisture of Curcuma dried from 3.167 db to 0.065 db with an air mass flow rate of 0.121 kg/s. The SAHPD reduced the drying time about 24% compared to HPD. The drying rate and the specific energy consumption were calculated in an average 1.05 kg/h and 1.36kg/h, and 1.17kWh/kg and 2.07kWh/kg for HPD and SAHPD, respectively. The specific moisture extraction rate and the dryer thermal efficiency were calculated in an average 0.931 kg/kWh and 0.521 kg/kWh, and 61.0% and 34.3% for HPD and SAHPD, respectively. Whereas, the pickup efficiency and the coefficient of performance of the heat pump were calculated in an average 57.5% and 59.2%, and 4.03and 4.35 for HPD and SAHPD, respectively. The SAHPD is capable of drying Curcuma quickly because of the high pickup efficiency and high drying rate.